Pengelolaan Manajemen Waktu Sebagai Kunci Keberhasilan Proses Pembelajaran Kelas VII di Mts Al-Mardliyyah - Ailsa Hayati Marsa Salsabila; Imalatul Hidayati; Fitriatul Laila Hasyim; Syaifurrahman Nabawi; Syaiful Haq (Action Research Journal, 2025)
The importance of time management in improving the academic achievement of seventh-grade students at MTs Al-Mardliyyah. Time management refers to students' ability to plan and use their study time effectively, ensuring that no time is wasted. Good time management helps students become more prepared, focused, and efficient in their learning, while also fostering discipline and a sense of responsibility. Supporting factors such as the roles of teachers and parents, as well as strategies like creating study schedules and setting priorities, play a significant role in successful time management. The results of the study show a strong relationship between time management and academic performance. Therefore, the implementation of effective time management is highly recommended as part of efforts to enhance the quality of education and support students’ overall character development, especially for seventh-grade students